1986
DOI: 10.1159/000298923
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bacterial Vaginosis with an Acid Cream: A Comparison between the Effect of Lactate-Gel and Metronidazole

Abstract: Bacteriological isolation of anaerobes, Gardnerella and lactobacilli was carried out in a group of 62 women with the diagnosis bacterial vaginosis and 42 control women. Lactobacilli were the predominant organisms in the control group whereas anaerobes dominated the flora in bacterial vaginosis patients. Lactate-gel (pH 3.5, 5 ml) inserted into the vagina daily for 7 days is as effective as oral metronidazole, 500 mg twice daily for 7 days. The women in both groups became symptom-free and objectively improved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
6

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 4 publications
2
34
0
6
Order By: Relevance
“…5-4 . 6) were comparable to those determined in the healthy vagina (Andersch et al, 1986;Tevi-Bénissan et al, 1997). Boskey et al (1999) reported that eight vaginal Lactobacillus strains acidified the growth medium to an asymptotic pH of 3 .…”
Section: Discussionsupporting
confidence: 85%
“…5-4 . 6) were comparable to those determined in the healthy vagina (Andersch et al, 1986;Tevi-Bénissan et al, 1997). Boskey et al (1999) reported that eight vaginal Lactobacillus strains acidified the growth medium to an asymptotic pH of 3 .…”
Section: Discussionsupporting
confidence: 85%
“…Acidification of the vagina has been tried by local application of products containing lactobacilli [4], lactic acid [5], hydrogen peroxide [6] and acetic acid [7]. A modern approach to decrease the pH, and consequently to get a long-lasting normalization of the vaginal flora, consists in the vaginal application of vitamin C (250 mg L-ascorbic acid) in the form of silicon-coated vitamin C tablets [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobes grow poorly at pH 4.5 or below [4]. The acid environment is maintained by the lactobacilli flora producing lactic acid [2], It has been shown that an acid gel is as effective as metronidazole for a short-term in BV [7]. Fifty percent of women treated with metronidazole relapsed after 2 months [8].…”
Section: Introductionmentioning
confidence: 99%